Comparative Microbial Profiles of Colonic Digesta between Ningxiang Pig and Large White Pig - Linfeng Lei; Zhaobin Wang; Jianzhong Li; Huansheng Yang; Yulong Yin; Bie Tan; Jiashun Chen (Animals, 2021)
Sixteen 35-day-old piglets, including eight Large White (LW) piglets (a lean-type pig breed) and eight Ningxiang (NX) piglets (a fatty-type Chinese Indigenous pig breed), were fed the same diet for 105 days. NX pigs had higher intramuscular fat content than LW pigs (p < 0.05). According to 16S rRNA gene sequencing, the relative abundances of the genera Ruminococcaceae_NK4A214_group, Parabacteroides, Christensenellaaceae_R-7_group and Ruminiclostridium were higher, whereas the abundances of Prevotellaceae_NK3B31_group, Prevotella, Subdoligranulum and Faecalibacterium were lower, in the colon of NX pigs compared to that of LW pigs. Nonmetric multidimensional scaling analysis revealed that the microbiota of the two pig breeds clustered separately along the principal coordinate axis. Furthermore, functional prediction of the bacterial communities suggested higher fatty acid biosynthesis in NX pigs. NX pigs also exhibited lower concentrations of total short-chain fatty acids, propionate and butyrate in the colon (p < 0.05). These findings suggest that NX pigs exhibited higher intramuscular fat content and backfat thickness than LW pigs. The bacterial communities in the colon of NX pigs were also more diverse than those in the colon of LW pigs, which might be used as a potential metabolomics mechanism to research different breeds of pigs.